Cardiac sarcoidosis in an adult person with cystic fibrosis: a case report - FitzMaurice, Thomas; Cooper, Robert; Snowdon, Richard; Arzanauskaite, Monika; Nazareth, Dilip; Walshaw, Martin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Cardiac sarcoidosis and cystic fibrosis (CF) are both rare conditions and their co-existence has not previously been noted in adults. For the first time we report a case of isolated cardiac sarcoidosis in a woman with CF, and discuss the possible combined aetiological factors. As the life expectancy of people with CF continues to increase, clinicians should be aware of the emergence of concomitant inflammatory conditions typically diagnosed in adulthood, and the diagnostic challenges this may present.